Analisis Penerapan Strategi Inkuiri dalam Pelajaran Sejarah Islam Kelas 4 KMI - Jaziela Huwaida; Popy Miftahul Jannah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2022)
One of the problems faced in the world of education today is that students are not encouraged to develop critical thinking skills to the fullest. Due to the lack of use of learning methods that can make students active and think critically. Thinking skills are one of the abilities that must be possessed by students in the 21st century. The implementation of the inquiry method in the learning process is to be able to invite students to be more active and be able to develop critical thinking skills toward the information or knowledge they have acquired. implementation of the inquiry method in developing critical thinking skills in Islamic history subjects in grade 4 KMI Gontor. The research method used is descriptive qualitative research. The research was conducted in class 4C KMI Gontor. Data collection techniques used interviews, observation, and documentation. The results of the study found that SKI teachers in grade 4 KMI Gontor could implement the inquiry method in developing students' critical thinking well. However, there are shortcomings at the stage of the inquiry method due to the limited time available. And the development of student’s critical thinking skills has begun to develop slowly and is well realized in students which are already implied at each stage of the inquiry method, but there are indicators of critical thinking skills that still need to be trained and accustomed because students have a quiet nature (introvert), shy, and lack of interest.